Senior Teacher Induction: An Alternative Apprenticeship Model for Pre Service Teacher - Syafi’i, Ahmad (Sebelas Maret University, 2016)
This paper reports on a case study on the role of Senior Teacher Induction (STI) in promoting pre service teachersâ pedagogical competence at STKIP Al Hikmah Surabaya. This study is an attempt to promote an alternative apprenticeship model for pre service teachers. Students in STKIP Al Hikmah have been permitted to enter host schools since the first semester. STKIP Al Hikmah incorporated blended learning approach within the curriculum. Activities in campus and at host schools were fully integrated. Students spent half of their time at host schools. They sat in classes taught by senior teachers. They had to observe activities done by the senior teacher such as how the teacher opened the class, how the teacher explained the materials, how the teacher interacted with his students, how the teacher managed the class, how the teacher assessed the studentsâ performance and so on. The students had to discuss with senior teachers after class for further information dealing with the class observation. Then, the students were asked to search any relevant references to support their findings. They had to note the result of the observation. Then, consult it to his supervising lecturer for comments and feedbacks. In addition, the students were challenged to design and modify their own teaching version. Eventually, they had to present their report in general stadium. The result of the research showed that 1) Senior Teacher Induction (STI) enabled to raise studentsâ pedagogical interest and involved them in class interaction in advance; 2) STI enabled the students to observe teaching skills they have to achieve as being future teachers